2018
DOI: 10.1177/0956462418785266
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of anorectal Chlamydia trachomatis infections in France through the lymphogranuloma venereum surveillance network, 2010–2015

Abstract: The objective of this article is to describe the epidemiology of lymphogranuloma venereum (LGV) and non-LGV Chlamydia trachomatis anorectal infections in France and to examine the characteristics of the affected populations via a voluntary sentinel surveillance system for LGV between 2010 and 2015. Anorectal samples positive for C. trachomatis (CT) were sent by the participating laboratories to the National Reference Center for CT for LGV identification. Biological and clinical data were collected by biologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…Outbreak investigations and surveillance data consistently showed that the majority of LGV cases occurred among HIV-positive MSM and that most of the cases presented with proctitis [2,4]. In contrast to previous reports showing that this profile of individuals with LGV has remained largely unchanged over the years, we found increasing proportions of HIVnegative and asymptomatic MSM among LGV-positives, up to almost 50% in 2017 [2,13,19,20].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Outbreak investigations and surveillance data consistently showed that the majority of LGV cases occurred among HIV-positive MSM and that most of the cases presented with proctitis [2,4]. In contrast to previous reports showing that this profile of individuals with LGV has remained largely unchanged over the years, we found increasing proportions of HIVnegative and asymptomatic MSM among LGV-positives, up to almost 50% in 2017 [2,13,19,20].…”
Section: Discussioncontrasting
confidence: 57%
“…In the Netherlands, the increasing number of LGV infections coincided with increasing numbers and positivity rates of gonorrhoea and infectious syphilis [17]. A rising trend in the number of LGV infections was also observed in France, which was explained by a combination of improved surveillance, better access to testing and an increasing incidence possibly due to increases in condomless anal sex among MSM [19]. Outbreak investigations and surveillance data consistently showed that the majority of LGV cases occurred among HIV-positive MSM and that most of the cases presented with proctitis [2,4].…”
Section: Discussionmentioning
confidence: 99%
“… The prevalence of HIV among MSM with LGV ranges from 67% to 100% in 13 descriptive studies. There is a significant association between HIV and LGV (odds ratio, 8.19, 95% CI, 4.68–14.33) (1,A) . Moreover, hepatitis C is associated with LGV in the current epidemic among MSM …”
Section: Managementmentioning
confidence: 99%
“…11 The same trend has recently been described in the United Kingdom 12 , Belgium 13 , Spain 14 and France. 15 In addition, the rising use of pre-exposure prophylaxis amongst MSM might be associated with more high-risk sexual behaviour and a subsequent increase of STIs. 16 As a result of this trend, a wide variety of medical specialists may encounter patients with LGV–related symptoms.…”
Section: Discussionmentioning
confidence: 99%